MENINGKATKAN PENGENALAN KOSAKATA BAHASA ARAB MELALUI PEMANFAATAN MEDIA GAMBAR PADA ANAK KELOMPOK B DI RA AL-JANNAH JAKARTA - Hanifah Nazarah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2017)
The acquisition of a child’s language is a poses of mastery of the child’s language experienced by the environment. Foreign language acquisition generally through informal and formal education. Learning media is anything that can be used to convey a message or information in the learning process so that it can stimulate the attention and interest of students in learning. Two-dimensional media can be a medium that quickly stimulates the attention and interest in children’s learning. Based on pre-research results in RA AL-Jannah Jakarta, the introduction of the vocabulary of Arabic children with a value of 29%. The method in this research is Classroom Action Research Method (PTK) with 2 cycles. In cycle I, there are 8 actions and 2nd cycle twice, with the success criteria reach 70%. Subjects in this study were at RA AL-Jannah Jakarta with 10 children aged 5-6 years consisting of 7 girls and 3 boys. Each cycle consists of four stages: planning, action, observation, and reflection. Data collection techniques through observation, field notes, interview notes and documentation. Data analysis uses data reduction, data presentation and conclusion. The results of this study note that 1) in the initial assessment of the ability of the vocabulary of Arabic language of children 29%, 2) after the child was given action in Cycle I, the ability of children began to increase to 65%, 3) Cycle II obtained results of 85%. So it can be concluded that the image media can improve the ability of the introduction of Arabic vocabulary of group B in RA AL-Jannah Jakarta.